Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If a quadratic in the form $y=ax^2+bx+c$ is reflected on the $y$ axis, why then must $b=0$, making the equation in the form of $y=ax^2+c$?

I can remember the rule, but the reasoning behind it has escaped me!


share|cite|improve this question
Do you mean "symmetric on the y-axis"? If so, then it's because you want $f(x) = f(-x)$ for all $x$, which is impossible if $b \neq 0$. – dsg Apr 7 '11 at 10:13
up vote 4 down vote accepted

The maximum of the generic $y = ax^2 + bx + c$ can be found via differentiation: $$x_\text{vertex}: 2ax_\text{vertex} + b = 0$$

If the shape is symmetric wrt the $y$ axis, then the vertex must lie on the $y$ axis itself, thus $x_\text{vertex} = 0$. This happens if and only if $b=0$.

Additionally, the intersections of the parabola with the $x$ axis must be such that $x_1 = -x_2 \implies$ $x_1 + x_2 = 0$, with $x_{1,2} = \frac{-b}{2a} \pm \overbrace{\frac{\sqrt{b^2-4ac}}{2a}}^\text{meh!}$. Thus, $x_1 + x_2 = \frac{b}{a}$, which is zero if and only if $b=0$.

Also see Wikipedia.

share|cite|improve this answer
Of course! Thanks! – MathsStudent Apr 7 '11 at 11:35

I think what you mean to say is that the quadratic is symmetric about the $y$-axis. What that implies formally is that $y(x) = y(-x)$. Try substituting the quadratic into that equation and see what happens.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.